Health-related quality of life and its association with the symptom score and the thyroid function status of patients with primary hypothyroidism on replacement therapy - Merina Martin; Rani Subramaniyan; Dhukhabandu Naik; Lakshmi Ramamoorthy; Hmar T Lalthanthuami (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: A number of patients with primary hypothyroidism have reduced health-related quality of life (HR-QoL), even with optimum thyroid hormone replacement therapy. This study aimed to assess the HR-QoL of patients with hypothyroidism under replacement therapy and identify its relationship with the symptom score and thyroid function status. MATERIALS AND METHODS: Using a cross-sectional study design, 175 hypothyroid patients under replacement therapy who visited the Endocrinology Outpatient Department of a tertiary care center were selected by convenient sampling technique. Data was collected using a structured data collection tool comprising, HR-QoL Short Form-36 questionnaire, and Zulewski's clinical score. Inferential statistical analyses were performed using Mann-Whitney U, Kruskal-Wallis, and Karl-Pearson Correlation tests. RESULTS: The overall mean quality of life score was 44.22 ± 12.14, with a substantial decline in role functioning because of physical health. A significant negative correlation (P < 0.05) was found between HR-QoL and hypothyroidism symptom score. A significant association was observed between participants' HR-QoL and their dosage of thyroxine supplement (P < 0.05,) but no association was found with thyroid function status. CONCLUSION: There was a substantial reduction in the quality of life of the patients despite being on thyroid replacement therapy and achieving euthyroid status. This underlines the importance of symptom reduction and hormone optimization to enhance the quality of life.